On the Link between Job Polarisation and Wage Inequality in Germany - Mario Reinhold (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
Job polarisation and increasing wage inequality is observed in many rich countries, including Germany. Both phenomena are well-discussed in international literature, though a link can only be observed in the U.S. I assess the impact of job polarisation upon wage inequality in Germany by benefitting from regional variation in job polarisation and applying distributional decomposition methods. Although wage inequality occurs nation-wide the dimension is profoundly larger in polarised labour markets, whereas two thirds of these differences can be explained by differences in the workforce. In contrast to the U.S., there are only slight hints of a direct relationship between occupational and wage changes. They fully vanish once accounting for shifts in skills within occupations. Eventually, the temporal patterns of job polarisation and wage inequality do not match, implying alternative reasons for the increase in wage inequality than occupational shifts.
Keywords: J31; J30; J33; 330